Thermodynamics of martensite formation in Fe–Mn–Al–Ni shape memory alloys. (February 2021) - Walnsch, Alexander; Kriegel, Mario J.; Motylenko, Mykhaylo; Korpala, Grzegorz; Prahl, Ulrich; Leineweber, Andreas
Abstract: Fe−Mn−Al−Ni based shape memory alloys are regarded suitable for large scale applications due to relatively low materials costs and a good cold workability. The austenitic state consists of an A 2 structured matrix with coherent B 2 precipitates which are required to ensure thermoelasticity, supposedly due to a strengthening effect on the matrix. The martensitic state is based on the A 1 structure. For a series of alloys, the martensite start temperatures were determined to be below ambient temperature, whereas for the same alloy compositions T 0 temperatures of about 1000 °C are predicted for the transformation of the A 2 matrix into A 1 by means of CalPhaD-based calculations. It is shown by thermodynamic considerations that the undercooling of about 1000 K is caused by the resistance of the B 2 precipitates ( NiAl with some content of Fe and Mn) to undergo the transformation to the L 10 structure enforced by the martensitic transformation of the matrix. Graphical abstract: Image, graphical abstract